Ultrasound-guided trigeminal nerve block and its comparison with conventional analgesics in patients undergoing faciomaxillary surgery: Randomised control trial - Kumar, Amarjeet (Indian J Anaesth, 2018)
BACKGROUND AND AIMS: Ultrasound (USG)-guided injection in pterygopalatine fossa is an indirect approach to block the trigeminal nerve. Trigeminal nerve block for maxillofacial surgeries may provide preemptive analgesia, reduce opioid consumption and opioid-related adverse effects. METHODS: In this randomised, prospective double-blind study, 60 American Society of Anesthesiologists I/II patients, within the age group of 18–60 years scheduled for faciomaxillary surgery (fracture/pathological lesion of maxilla or mandible and cleft lip), were recruited. The patients were allocated in either of the two groups: group I: general anaesthesia (FENT group) and group II: general anaesthesia + trigeminal nerve (TNB group). Perioperative opioid consumption and postoperative pain scores were recorded. Any adverse effects like respiratory depression and nausea were also looked for. RESULTS: Patients in group II required less intraoperative fentanyl top ups (1.17 ± 0.53 vs 2.70 ± 0.53) (P < 0.05). Postoperative opioid consumption was also less in this group (0.93 ± 0.69 vs 3.53 ± 0.68) (P < 0.05). CONCLUSION: USG-guided TNB reduces perioperative opioid consumption in patients undergoing faciomaxillary surgery with better patient pain scores.